Herbarium Celebense (CEB) History, Research Activity and Achievement (2000-2007) - Ramadhanil Ramadhanil (Biocelebes, 2007)
Sulawesi is the largest island in the Wallacea subregion of Indonesia. The island is rich in endemic species, yet scientific knowledge of the plants of Sulawesi is still very limited. There is a lack of botanical exploration, publications, and infrastructure. In 2000, the Tadulako University (UNTAD) of Palu, Sulawesi, in coorporation with the University of Göttingen (Germany), Bogor Agricultural University (IPB), National Herbarium of Netherlands (L), Leiden, Herbarium Bogoriense (BO), and Herbarium Wanariset (WAN), and with the support of the German Research Foundation (DFG), has constructed a Herbarium in Sulawesi, the Herbarium Celebense, registered with the Index Herbariorum (New York) as CEB. The Herbarium Celebense currently holds approximately 10.000 plant specimens, especially from Central Sulawesi, including mainly spermatophytes. Some of them are collection of Type specimens. Key words: Indonesia, Wallacea region, Central Sulawesi, Herbarium Celebense